An analytical frequency response function for fluidelastic instability model of a normal triangular array in cross-flow - Alyaldin, Loay; Mureithi, Njuki W. (Journal of sound and vibration, 2023)
A new model based on Theodorsen’s classical theory of aerodynamic instability and the mechanism of flutter is proposed to explain the origin of the time delay, an important parameter for fluidelastic instability prediction, between the tube motion and the non-linear fluidelastic forces. Using this model, a novel time delay function has been theoretically derived with no reliance on unsteady fluid force data, as was the case with earlier models. A stability analysis is carried out based on the new time delay function combined with the experimental static fluid forces for a range of mass damping parameters. The predicted stability threshold is found to compare well with experimental stability data.